El viaje como diálogo con el lector: la experiencia epistolar - Marotta, Mirella (Revista de Filología Románica, 2006)
This article shows how the letter is one of the best loved forms for travel writers. The most important part of the letter is the first line, where the traveller tells the date and place where he has taken the pen. The first line is a veracity insurance for the Travel Recit.